Direct anterior Hueter approach is a safe and effective approach to perform a bipolar hemiarthroplasty for femoral neck fracture: Outcome in 82 patients. (4th May 2015) - Langlois, Jean; Delambre, Jérôme; Klouche, Shahnaz; Faivre, Bruno; Hardy, Philippe
Abstract : Background and purpose — The direct anterior (DA) approach in total hip arthroplasty has recently been associated with faster functional recovery than the posterolateral (PL) approach. We hypothesized that the same should hold for the DA approach in bipolar hemiarthroplasty for femoral neck fractures. Patients and methods — 82 patients with a displaced femoral neck fracture and candidates for bipolar hemiarthroplasty were enrolled after IRB approval in this prospective non-randomized comparative study (DA: n = 38; PL: n = 44). The postoperative protocols were similar in both groups. Evaluation included surgical complications, component placement, and early functional outcomes, assessed 6 weeks postoperatively using a timed up-and-go (TUG) test. The incidence of dislocation was assessed by telephone interview at least 1 year after the surgery. Results — The DA-group patients had better results in the TUG test than the PL-group patients 6 weeks after surgery: half were under 19 seconds as opposed to only one third for PL (p = 0.06). We did not record any intraoperative femoral fracture or any lateral femoral cutaneous neuropraxia in the DA group. We observed a significant difference (p = 0.04) in lateral offset between the PL group (4.2 (SD 6.4) mm) and the DA group (−1.6 (SD 8.5) mm). Stem alignment was similar between groups. The dislocation rate for DA patients was lower than for PL patients (1 of 38 cases vs. 9 of 44 cases; p = 0.02). Interpretation — Our findings indicate that relative to the posterolateral approach, the direct anterior approach for bipolar hemiarthroplasty may improve gait in the early postoperative period and decrease the dislocation rate.